The intercondylar fossa—A narrative review. Issue 1 (24th August 2021) - Hirtler, Lena; Kainberger, Franz; Röhrich, Sebastian
Abstract: The intercondylar fossa ("intercondylar notch, " IN) is a groove at the distal end of the femur, housing important stabilizing structures: cruciate ligaments and meniscofemoral ligaments. As the risk for injury to these structures correlates with changes to the IN, exact knowledge of its morphology, possible physiological and pathological changes and different approaches for evaluating it are important. The divergent ways of assessing the IN and the corresponding measurement methods have led to various descriptions of its possible shapes. Ridges at the medial and lateral wall are considered clinically important because they can help with orientation during arthroscopy, whereas ridges at the osteochondral border could affect the risk of ligament injury. Changes related to aging and sex differences have been documented, further emphasizing the importance of individual assessment of the knee joint. Overall, it is of the utmost importance to remember the interactions between the osseous housing and the structures within.